Wildlife laws monitoring as an adaptive management tool in protected area management in Ghana: a case of Kakum Conservation Area - Wiafe, Edward Debrah (SpringerPlus, 2016)
INTRODUCTION: The wildlife laws of Ghana alienated the rural communities from forests and material well-being depended upon for their livelihood and this manifests itself in the progressive conflict between the park patrol staff and poachers from the fringes of the protected areas. CASE DESCRIPTION: The main aim of this study was to determine the impact of quantification of patrol efforts on indicators of illegal hunting activities that occur in rainforest protected areas, as a result of monitoring patrol operations and modifying the original plan. The specific objectives were to determine the optimal patrol efforts necessary to reduce illegal wildlife use to minimal; and the influence of the rainfall and seasonal activities on illegal wildlife use. DISCUSSION AND EVALUATION: The results indicated that as the patrol efforts increased the encounter with illegal wildlife use also increased until a certain point that the encounter rates started decreasing. Neither rainfall nor seasonal activities influenced the illegal activities and the patrol efforts. The protection staff of rainforest protected areas would work effectively to bring down illegal wildlife off-take to the barest minimum if monitored, quantified and provide feed-back. CONCLUSIONS: Illegal wildlife off-take can also be reduced by the protection staff if the original plans are made flexible to be adjusted. Recommendations for further studies have been made.

Built to improve: Leveraging realtime M&E for adaptive youth employment programming - Skelton, John (Prospects practice paper, 2, 2016)
Recognising that aid and development programming takes place in complex contexts, Mercy Corps is increasingly seeking to understand how best to manage programs which iterate, adapt and respond to the consistently evolving settings in which we work. This brief Practice Paper provides some examples of what adaptive management looks like in practice on the Prospects youth employment program in Liberia. It does not seek to function as a manual or set of guidelines, but simply provides some practical examples and insights into how a youth employment program governed by principles of adaptive management operates.

Introduction to SAVI's way of working - State Accountability and Voice Initiative (SAVI) - SAVI (DFID, 2015)
We are piloting a new approach to identifying and supporting our partners.  This breaks with convention in many ways in order to improve impact.  SAVI Approach Papers summarise key aspects of SAVI’s way of working. They explain what we do, and why – and link to relevant tools and frameworks. Our approach is summarized in...
Keywords: Practice

Nigeria Public Sector Accountability and Governance Programme - Business Case - SAVI (DFID, 2016)
In May 2016, SAVI transitioned into a successor programme – the ‘Engaged Citizens Pillar’ (ECP) of a wider DFID-funded governance reform programme ‘The Partnership to Engage, Reform and Learn’ (PERL). ECP is managed by the same service provider, Palladium, and the same core management team as SAVI, and many of the SAVI front line staff...

SAVI Approach Paper 1: Core Values - SAVI (London, 2015)
Governance reform is about government and citizens working together in more responsive, inclusive and accountable ways for the benefit of citizens. More responsive, inclusive and accountable attitudes and behaviour on the part of government and non-government stakeholders are the critical factors which lead to meaningful reform processes, and replicate and sustain reforms beyond the lifetime...

SAVI Approach Paper 10: Engaging State Governments - SAVI (DFID, 2015)
SAVI as a programme does not directly work with state governments – but we work in close conjunction with sister programmes who are supporting state governments on governance and sector reforms. SAVI supports non-government and SHoA partners to play their part in promoting more responsive, inclusive and accountable state governance delivering better services for citizens....

SAVI Approach Paper 11: Managing and Staffing an Adaptive Citizen Engagement Programme - SAVI (DFID, 2016)
SAVI, a DFID funded programme implemented by Palladium, is an adaptive programme putting learning and adaptation at the centre of all decision-making. In relation to management and staffing SAVI has established the following approaches to facilitate this: – An adaptive approach to programme management: Full time strategic technical leadership, that works closely with and complements...

SAVI Approach Paper 12: Managing Programme Finances to Support Adaptive, Locally-led Processes of Citizen Engagement in Governance - SAVI (DFID, 2016)
SAVI, is seeking to support processes of citizen engagement in governance in ways that are effective in influencing reform, and that are able to take on a life of their own without continuing donor support. SAVI is also an adaptive programme, putting learning and adaptation at the centre of all decision-making. Money is used and...

SAVI Approach Paper 13: Measuring Value for Money and using Value for Money Analysis - SAVI (DFID, 2016)
SAVI has established its own framework for assessing Value for Money in annual performance – in relation to expenditure, economy, efficiency, effectiveness and equity. Routine tracking and analysis of expenditure and economy ensure that inputs are supplied and services delivered to partners in line with SAVI’s core values, whilst also meeting DFID requirements and competing...

SAVI Approach Paper 14: Learning, Adaptation and Communications - SAVI (DFID, 2016)
SAVI, a DFID funded programme implemented by Palladium, is an adaptive programme, aiming to put learning and adaptation at the centre of all decision-making. Learning and adaptation takes place in SAVI at three levels: the work of partners; the work of SAVI delivery teams; and the enabling environment of the programme as a whole. Achieving...

SAVI Approach Paper 15: Introduction to PERL: the SAVI Successor Programme - SAVI (DFID, 2016)
In May 2016, SAVI transitioned into a successor programme – the ‘Engaged Citizens Pillar’ (ECP) of a wider DFID-funded governance reform programme ‘The Partnership to Engage, Reform and Learn’ (PERL). ECP is managed by the same service provider, Palladium, and the same core management team as SAVI, and many of the SAVI front line staff...

SAVI Approach Paper 2: Programme Design - SAVI (DFID, 2015)
SAVI supports citizen engagement in governance through a facilitated partnership approach, in contrast to the usual approach of grants to civil society organisations (CSOs). The overall aim is to facilitate and support working relationships and processes of reform that are home-grown, self-sustaining and, after initial engagement, not dependent on external support. Our way of working...

SAVI Approach Paper 3: Theory of Change - SAVI (DFID, 2015)
SAVI’s theory of change is a simple, practical guide that staff and partners use to plan and to monitor change – as well as to reflect on and enhance their own effectiveness. It sets out broad stages of attitude and behaviour change over time to facilitate effective citizen engagement in governance processes, systems and structures....

SAVI Approach Paper 4: Thinking and Working Politically - Supporting partners and staff through a participatory apporach to political economy analysis - SAVI (DFID, 2015)
Thinking and acting politically is central to the SAVI programme. We support staff and partners to analyse the power relations that shape change in their state, and to use this knowledge to inform their decision-making. This includes decisions made by SAVI state teams relating to the issues and partners they engage with and support, and...

SAVI Approach Paper 5: Defining and Measuring Results - SAVI (DFID, 2015)
SAVI aims to facilitate replicable and sustainable processes of citizen engagement in governance. The programme in each state is locally defined, flexible and adaptive, and results are not predictable in advance. Standardised monitoring tools are not applicable, and consequently we have evolved our tools and frameworks during the programme through processes of learning by doing....

SAVI Approach Paper 6: Engaging Civil Society - SAVI (DFID, 2015)
SAVI state teams provide support to CS groups to become more effective agents of citizens’ voice and public accountability, through a variety of mutually reinforcing interventions. These include: hands-on support to demonstration civil society Advocacy Partnerships (APs) facilitating working partnerships between civil society APs, SHoAs, and the media brokering working relationships between all of these...

SAVI Approach Paper 7: Promoting Gender Equality and Social Inclusion - SAVI (DFID, 2015)
We promote attention to gender equality and social inclusion in all of our engagement with CS groups, the media and SHoAs, and in all of the issues and processes they work on. In all the states we work in, we also support partners to focus on some issues and form some partnerships and networks which...

SAVI Approach Paper 8: Engaging the Media - SAVI (DFID, 2015)
The overall aim of SAVI engagement with the media is for media representation of citizens’ interests to become normal, and play its part in helping state governments to be more responsive, inclusive and accountable to their citizens. Media partners – individual media personnel and selected media houses – are supported to be more effective agents...

SAVI Approach Paper 9: Engaging State Houses of Assembly - SAVI (DFID, 2015)
The overall aim of SAVI engagement with SHoAs is to promote lasting reforms that are not dependent on external funding and which promote an increasingly more responsive and accountable relationship between Nigerian state governments and their citizens. SHoAs are supported to be more effective agents of citizen voice and public accountability, demanding better performance from...

State Accountability and Voice Initiative (SAVI) - Approach Paper Series - SAVI (DFID, 2016)
We are piloting a new approach to identifying and supporting our partners.  This breaks with convention in many ways in order to improve impact. Our approach is summarized in the Introduction to SAVI’s way of working. We have broken our approach down into key components – depicted in the form of our ‘knowledge tree’ –...
Keywords: IMPORTANT

Adaptive Programming in Fragile, Conflict and Violence-Affected Settings, What Works and Under What Conditions?: The Case of PERL, Nigeria - Punton, Melanie; Burge, Richard (Action for Empowerment and Accountability Research Programme, 2018)
This paper examines adaptive approaches to aid programming in Nigeria. Through field research and desk reviews, we have investigated some of the assertions around the ‘adaptive management and programming’ approach, which has arisen in recent years as a response to critiques of overly rigid, pre-designed, blueprint and linear project plans. This is the second of three case studies in a series which explore if and how adaptive approaches, including rapid learning and planning responses, are particularly relevant and useful for promoting empowerment and accountability in fragile, conflict and violence-affected settings (FCVAS). This case study focuses on PERL (Partnership to Engage, Reform and Learn) in Nigeria, a five-year governance programme (2016-21) with a total budget of £100 million. It aims to promote better service delivery through bringing together government and citizens groups to collectively address governance challenges. PERL is viewed by DFID as the final stage of a 20-year investment, building on learning, experience and partnerships from 15 years of DFID-funded governance programming in Nigeria. It was designed to incorporate learning and adaptation through a ‘living’ theory of change, continuous political economy analysis at different levels, adaptive implementation by location-based delivery teams who are encouraged to be flexible and let partners take the lead, regular learning and reflection, and adaptive resourcing, HR and administrative systems. The case study draws on a conceptual framework (the ‘adaptive triangle’) that looks at three types of adaptation – adaptive management, adaptive programming and adaptive delivery – and the interconnections and tensions between them.
Keywords: A4EA; Adaptive Development; Economy; Fishery

‘We have the solutions to our own problems’: supporting civil society in Nigeria - Overseas Development Institute (ODI, 2014)
Development assistance programmes that start from careful analysis of what works and what does not in country contexts are still remarkably rare. One reason for this is the lack of well documented examples of ‘politically’ smart aid programming. To this end, this film outlines the experience of the State Accountability and Voice Initiative (SAVI), a DFID-funded programme in Nigeria providing support to civil society, media and governmental organisations.

How Does the World Bank Build Citizen Engagement Commitments into Project Design? Results from Pilot Assessments in Mozambique, Myanmar, Nigeria, and Pakistan - Nadelman, Rachel; Le, Ha; Sah, Anjali (Working Paper 525, 2019)
How and to what degree is the World Bank putting its new institutional citizen engagement (CE) commitments into practice? This question guides an independent assessment that the Accountability Research Center (ARC) at American University has undertaken as part of the Institute of Development Studies-led Action for Empowerment and Accountability (A4EA) research programme’s investigation into how external actors can best support local processes of and conditions for empowerment and accountability. This report investigates the World Bank’s incorporation of CE into project design, the critical early stage of donor engagement. To accomplish this, ARC reviewed the World Bank’s fiscal year 2015–17 investment project portfolios for four A4EA priority countries, Mozambique, Myanmar, Nigeria, and Pakistan, which covers 57 projects that range from US$19 million to U$600 million. The analysis determines whether projects commit to seeking a strategic approach to CE, which involves combining multiple tactics so that the whole could be greater than the sum of the parts. This assessment of CE commitments is intended to help to inform possible national, civil society organisation strategies to monitor whether and how these commitments are actually implemented in practice.

Case study: Embedding reform and exiting: LASER’s application of the hourglass approach to achieve sustainable results - Manuel, Clare (DFID-LASER Programme, 2016)
This case study describes how LASER has gone about enabling systemic change and sustainable uptake of reforms that address complex institutional problems in Kenya, Rwanda, Sierra Leone, Somaliland and Uganda. In each of these countries LASER has designed-in a sustainable approach from the start based on: (i) local ownership and leadership of reforms based on developing country (rather than donor) priorities; (ii) use of country (rather than donor programme) systems; and (iii) an understanding that the role of the donor / development practitioner is to support (rather than buy) reform. The case study uses LASER’s hour glass methodology, illustrated with examples from LASER interventions, to show how these principles guide LASER operations every step of the way.
Keywords: IMPORTANT; Practice

Adaptive Management in Practice: a case study on the Prospects program - Maclay, Chris (Prospects practice paper, 1, 2016)
Recognising that aid and development programming takes place in complex contexts, Mercy Corps is increasingly seeking to understand how best to manage programs which iterate, adapt and respond to the consistently evolving settings in which we work. This brief Practice Paper provides some examples of what adaptive management looks like in practice on the Prospects youth employment program in Liberia. It does not seek to function as a manual or set of guidelines, but simply provides some practical examples and insights into how a youth employment program governed by principles of adaptive management operates.

Thinking and Working Politically: Lessons from FOSTER in Nigeria - Lopez Lucia, Elisa; Buckley, Joanna; Marquette, Heather; McCulloch, Neil (Research Paper, 2017)
The Facility for Oil Sector Transparency and Reform (FOSTER) was a £14 million programme that has helped Nigeria to transform its governance of the oil and gas industry. FOSTER ran from 2011 to mid-2016, and used an explicit ‘thinking and working politically’ (TWP) approach. It was funded by the UK Department for International Development (DFID) and managed by Oxford Policy Management (OPM). This paper seeks to identify the factors that drove – or constrained – FOSTER’s achievements, and asks what this can tell us about TWP, particularly in challenging political and sectoral contexts. FOSTER sought to help strengthen oversight and accountability in Nigeria’s oil sector. It aimed to support reformers within government institutions that ‘supply’ accountability (those governing how oil and gas revenues are collected and managed), and to support civil society organisations, parliament, the media and the Nigeria Extractive Industries Transparency Initiative to ‘demand’ reform. In addition, FOSTER commissioned a series of studies and provided media training to help broaden understanding of the sector and highlight the need for reform. This paper examines the outcomes from five ‘clusters’ of FOSTER interventions. The FOSTER team viewed the first three of these in the list below as successful, whereas the latter two did not deliver on expectations but offer important opportunities for learning: • Support to the Nigerian Extractive Industries Transparency Initiative • Support to demand-side actors to promote transparency and accountability in the oil sector • Support for the passage of the Petroleum Industry Bill • An oil spill-mapping social media project • Support to the Department of Petroleum Resources The analysis drew on 44 semi-structured interviews conducted during a month of fieldwork in Abuja and Lagos; on reviews of the programme’s monitoring, evaluation and learning frameworks; and on newspaper articles and grey literature on Nigeria’s oil sector.2

Enabling citizen-driven improvement of public services. Leveraging Technology to Strengthen Accountability in Nigerian Healthcare - ICT4SA (World Bank and Reboot, 2015)
Effective public service delivery begins with knowing whether the services offered are working as intended. We launched a system to enable citizen input on the delivery of public services.

Adaptive programming in practice: shared lessons from the DFID-funded LASER and SAVI programmes - Derbyshire, Helen; Donovan, Elbereth (Synthesis Paper 3, 2016)
LASER synthesis papers aim to help donors and other stakeholders better understand why and how to approach investment climate reform programming differently. The papers reflect emerging best practice and lessons learnt on what works and what does not work in doing development differently. The papers have been peer-reviewed by experts in the field including senior advisers at DFID, World Bank, IFC and the Donor Committee for Enterprise Development (amongst others).
Keywords: IMPORTANT; Practice

Strengthening Advocacy and Civic Engagemetn in Nigeria - Chemonics (Chemonics International, 2018)

Participation by All - The keys to sustainability of a CRS food security project in Niger - Cekan, Jindra; Kagendo, Rutere; Towns, Alexandra (Valuing Voices, 2016)
This project that ran from 2006-2012 in Niger and was implemented by three NGOs: CRS, Cooperative for Assistance and Relief Everywhere (CARE), and Helen Keller International (HKI) under the direction of United States Agency for International Development (USAID) Office of Food for Peace (FFP) as a multi-year assistance program (MYAP) to support food security activities in the Dosso, Tahoua, and Zinder regions. PROSAN focused on increasing agricultural production and agro-enterprise, improving household health and nutrition status, reinforcing the capacities of health agents, and enhancing community resiliency. Here are the highlights from the report which itself is an excerpt from a longer analysis we did. Also please note one Annex highlights the similarlties/ differences we found to USAID/ FFP’s 4 elements of sustainability: AIM, METHODS, AND RESEARCH QUESTIONS The aim of this sustainability evaluation was to explore perceptions of sustainability from Nigeriens involved in PROSAN, former CRS staff and donors. It focused on evaluating participants’ adherence to project outcomes and their creation of new innovations. It also evaluated partners’ involvement in sustaining project outcomes. This evaluation used qualitative and quantitative methods including community mapping, focus group discussions, beneficiary interviews, and key stakeholder interviews. The evaluation was carried out in six communities in the Dosso region, with more than 500 interviewees, focusing on the following research questions: Sustainability of activities and groups: Are the communities sustaining the activities three to five years after the end of the project? What can we learn from the communities and their post-project implementation partners? Spread and unexpected outcomes: If the project was considered a success in the eyes of the community, how well did it spread? Fostering Sustainability: What are the long-term prospects for continued sustainability? FINDINGS Three years after PROSAN’s conclusion, the project was considered a success by community members, national partners, the implementer (CRS), and donor (USAID) staff. The main findings include: 1. SUSTAINABILITY OF ACTIVITIES AND GROUPS Eighty percent (80%)[*] of all activities were reported to have become self-sustained and community innovations have emerged: On average, households reported moving from being food secure for 3-6 months per year during PROSAN to 8-12 months at the time of this evaluation, which is a remarkable impact [1]. CRS_Niger_PROSAN_Sustainability_Evaluation_pdf [1] Women reported greater income through the increase in sales of food that was produced and processed due to the grain mills [1]. Respondents also reported improved household health, hygiene, and nutrition, with 91% of survey respondents indicating that their health and sense of well being had improved, especially through the efforts of the health posts and clinics that CRS helped build and the government of Niger’s efforts in sustaining them with resources and staff [1]. Community groups/committees have continued and are well-supported by NGO partners: 81% of the committees set up by PROSAN were functioning at the time of this evaluation, with many participants discussing ways to sustain best practices within their communities, and members still receiving regular trainings or updates [1]. Several new and refresher trainings come through national partners, NGOs, and new channels such as radio programs [1]. Some new NGOs and international organizations have built upon PROSAN’s success, for instance, by using land previously managed by PROSAN for a new vegetable gardening training program, building hygiene programs on past health awareness efforts, or extending agricultural credit for further inputs [1]. Twenty percent (20%) of implemented activities were not sustained or have stagnated: While hygiene practices were sustained by households and there was widespread latrine construction, sanitation was poor in the villages, and most latrines had fallen into disrepair [1]. Fewer than 50% of women reported practicing exclusive breastfeeding for children less than six months of age [1]. While almost half of all health committees no longer exist, new health clinics staff have replaced some of the work of the committees with health and agricultural promotion messages now being sent via radio, television, and cell phones [1]. Literacy training and theater groups have completely ceased [1]. With the exception of the Système Communautaire d’Alerte Précoce-Réponses aux Urgences’ (SCAP-RU) SCAP-RU early warning system which has expanded, other resilience activities such as roadwork and caring for the environment are a lesser priority due in part to the lack of food and cash-incentives to continue doing them [1]. 2. SPREAD AND UNEXPECTED OUTCOMES New innovations and ceased activities reflected the project’s legacy: Community innovations have emerged such as collective funds paying for cleaners of the new health center, community-imposed sanctions for births occurring outside of the health centers, and the monitoring of savings from well water sales. National partners have praised the project, with many lamenting its withdrawal. One non-PROSAN village told an Agriculture Ministry staff and potential NGO partner that “No one should bring a program here unless it is like PROSAN.” PROSAN-trained masons, well repair technicians, and village youth have learned land recuperation techniques (zai holes, bunds and demi-lunes) that helped generate income beyond project communities. Project activities that received free inputs have largely stopped being implemented once the incentives were withdrawn such as Food for Training (FFT), Food for Work (FFW), or Cash for Work (CFW) (e.g. literacy, seedlings, latrines, theater etc.); nonetheless the inputs were highly valued and have continued to support agriculture and health (carts, bicycles). 3. FOSTERING SUSTAINABILITY The following areas were identified as potential barriers to sustainability that could be systematically explored in other projects: Although most committees are still functioning, there are no processes in place to engage and train youth and new inhabitants of the villages. While village communities have been maintained, there is an increasing lack of ministry resources (e.g., staff, transportation, and communications) to take the place of NGOs like CRS after a program ends. There is little management of knowledge around project data, which is further exacerbated by staff changes in NGOs, government ministries, and donors. Project data (proposal content, monitoring data, evaluation results, participant lists, partner names, and exit agreements) must be managed ethically, locally and be held online, accessible for future projects to use and for villages to conduct self-evaluations.

Implementing Adaptive Approaches in Real World Scenarios: A Nigeria Case Study, with Lessons for Theory and Practice - Bridges, Kate; Woolcock, Michael (The World Bank, 2019)
How does adaptive implementation work in practice? Drawing on extensive interviews and observations, this paper contrasts the ways in which an adaptive component of a major health care project was implemented in three program and three matched comparison states in Nigeria. The paper examines the bases on which claims and counterclaims about the effectiveness of these approaches were made by different actors, concluding that resolution requires any such claims to be grounded in a fit-for-purpose theory of change and evaluation strategy. The principles of adaptive development may be gaining broad acceptance, but a complex array of skills, expectations, political support, empirical measures, and administrative structures needs to be deftly integrated if demonstrably positive operational results are to be obtained, especially when undertaken within institutional systems, administrative logics, and political imperatives that are predisposed to serve rather different purposes.

The SAVI programme in Nigeria: Towards politically smart, locally led devlopment - Booth, David; Chambers, Victoria (ODI, 2014)
 More examples are needed of aid programming that works by being responsive to country realities: politically smart, problem-driven and locally led  DFID’s SAVI programme has revealed a hitherto untapped potential for change leading to better development results at state level in Nigeria  SAVI provides low-profile support to state-level organisations and partnerships, building their capacity to engage constructively with government  It avoid the pitfalls of a donor-driven approach by ‘taking the money off the table’  This illustrates the power of facilitated multi-stakeholder engagement and the disadvantages of seeing this in terms of ‘supply side’ and ‘demand side’ governance  The set-up of the DFID suite of state-level programmes, with separately managed sector support and ‘governance’ initiatives, has limited realisation of the potential  Key enabling conditions were that DFID provided space for an experience-based design process and permitted tangible results to be judged retrospectively, not pre-programmed

Politically smart support to economic development: DFID experiences - Booth, David (ODI, 2016)